Cassava starch appraisal during fermentation and biscuit making processes - Ascheri, Diego Palmiro Ramirez; Vilela, Evodio Ribeiro (Pesquisa Agropecuaria Brasileira, 1995)
The occurrence of alterations in sour starch due to time allocated for fermentation has been observed in experiments with natural fermentation. Products obtained showed a variation in chemical composition, drop of viscosity in the dough and increase in percentage of starch harmed, yeast raise potential and soluble index to 50 °C, 70 °C and 90 °C. Parameter variation was greater for starches obtained in industrial tanks. Yeast expansion and density of biscuits allowed for starch quality, permitting the detection of the optimal point thirty days after the fermentation process occurs.